Cognitive Bias and its Relationship to Learning Motivation among Umm Al-Qura University Students - Hammad, Dayana Fahmi Ali; Baothman, Shuruq Abdullah Muhammad (Journal of Educational and Psychological Sciences, 2023)
The current study, aimed to determine levels of cognitive bias and learning motivation among Umm Al-Qura University students. It also sought to identify correlation between the two variables. Study sample consisted of (495) male and female students at Umm Al-Qura University. The descriptive correlative methodology was utilize to achieve study’s aims, and data were collected using two scales, the first one was for cognitive bias (Al-Adli, 2017), while the other one was for learning motivation (Al-Mutairi, 2019). Results indicated that level of cognitive bias was moderate, whereas high for learning motivation. The correlation coefficient between the two variables was (0.17), which reveal weak relation between them. In light of these findings, the study recommends applying strategies and methods that support the objective processing of information using logical thinking in order to reduce cognitive bias caused by self-expectations, as well as urging students to consider existence of various perspectives before making decisions and to accept ideas of other party through constructive dialogue, furthermore urging parents during upbringing process to provide alternatives to their children without expectations or demands to choose.